The use of whatsapp cooperative learning to improve writing ability - Ni Nyoman Yuliantini; I Gusti Ayu Dewi Paramita; Evin Yudhi Setyono; Ni Ketut Suciani (Politeknik Negeri Bali, 2021)
English is one of the primary subject that was taught in Electronic Engineering, Politeknik Negeri Bali, which includes speaking, writing and listening. Other than speaking, writing also become one of the most challenging subject in Electronic Engineering. To overcome the low writing skills of students and create pleasant learning atmosphere during the Covid 19 Pandemic, the authors want to try out learning method, namely Cooperative Learning Method with online media in the form of whatsapp. This research is a quantitative research with quasi experimental approach. The groups used in this study consist of two groups namely the experimental group using Whatsapp Cooperative Learning methods and the control grouos using the conventional method. The data collection technique in this study was in the form of a questionnaire and given to the students in both classes. From the data, it can be concluded that learning with the Whatsapp Cooperative Learning method is more effective to be used in teaching writing. It can be seen from the value of 2 of -2, 087 with Sig 0,037< 0,05 means that there is significant difference between the control class and the experimental class. This significant difference can be said as the result of the use of Whatsapp Cooperative Learning in class.